Patient comfort factors associated with the chronically implanted extravascular ICD (EV ICD): retrospective analysis of the first-in-human EV ICD trial. (25th November 2020) - Kotschet, E; Crozier, I; Haqqani, H; Alison, J; Thompson, A; Sherfesee, L; O'Donnell, D
Abstract: Background: The extravascular ICD (EV ICD) utilizes a lead positioned within the substernal space and a device placed along the left midaxillary line to provide pacing and defibrillation therapies. Since substernal implantation positions the lead close to the heart, a lower energy for defibrillation is needed for the EV ICD relative to an ICD with subcutaneous lead placement. With lower energy requirements, the EV ICD system requires only a 33 cubic centimeter (cc) device, whereas the commercially available subcutaneous ICD utilizes a ∼60 cc device. The smaller form factor for EV ICD may require a smaller device incision site with smaller pocket, potentially resulting in less post-operative pain. Figure 1 illustrates the comparative sizes of the EV ICD and a subcutaneous device. While issues related to patient comfort have been published for the subcutaneous ICD, patient comfort factors associated with the EV ICD system have not been described previously. Purpose: To characterize post-operative factors related to patient comfort associated with the EV ICD system. Methods: The EV ICD first-in-human study was conducted at four sites in Australia and New Zealand. Data from chronically implanted patients were retrospectively analyzed for changes in analgesics in the post-operative window between implant and the two-week follow-up. Adverse events were collected between implant and six months related to patient-reported pain/discomfort, need for system revision based on discomfort, impaired wound healing and seroma formation. Results: In total, 21 patients underwent implantation of the EV ICD system. Three patients had initiated pain control medications prior to enrollment, including one patient with fractured ribs. Overall, 12 patients (57.1%) received no anesthetic or analgesic medications besides acetaminophen beyond the day of implant. For the remainder of patients, post-operative medications included fentanyl (1), discontinued after two days; morphine (4), discontinued the day of implant (1) or after ≤2 days (3); or oxycodone (10), discontinued after ≤1 day (7) or ≤1 week (3). There were no intraprocedural complications. There were four non-serious, early-onset (≤1 week post-implant) adverse events identified, which included swelling (1), impaired healing at the xiphoid incision site (1), and two instances of inspiratory pain ≤1 day post-implant, all of which resolved without sequelae. There were no system revisions or removals associated with incision sites or pocket discomfort, and there were no reports of seroma formation through six months of follow-up. Conclusions: Analysis of factors related to patient comfort indicate that the EV ICD system has generally been well tolerated across patients. A larger data set is needed to more fully characterize whether the smaller device size of the EV ICD relative to the subcutaneous defibrillator results in improved patient comfort. Funding Acknowledgement: Type of funding source: Private company. Main funding source(s): Medtronic plc